Terpenes and Terpenoids 2018
DOI: 10.5772/intechopen.73215
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes from Natural Products with Potential Anti-Inflammatory Activity

Abstract: The development and progression of many diseases is related with an inflammatory process, which could affect different organs or tissues. Currently, many drugs are used to treat inflammation. However, some of these compounds induce severe side effects. For this reason, the search of new therapeutic options for the treatment of inflammation is very desirable. Medicinal plants have been an interesting source for obtaining new active compounds, including several terpenes and terpenoids with anti-inflammatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Terpenoids are terpenes derived compounds containing additional functional groups [ 84 ]. Examples of terpenes with anti-inflammatory actions include d-limonene, acanthoic acid, terpinolene, linalool, α-pinene, α-terpineol, α-phellandrene, and γ-terpinene [ 84 , 85 , 86 ].…”
Section: The Anti-inflammatory Compounds Present In the Diet: Classification And Mechanism Of Actionmentioning
confidence: 99%
“…Terpenoids are terpenes derived compounds containing additional functional groups [ 84 ]. Examples of terpenes with anti-inflammatory actions include d-limonene, acanthoic acid, terpinolene, linalool, α-pinene, α-terpineol, α-phellandrene, and γ-terpinene [ 84 , 85 , 86 ].…”
Section: The Anti-inflammatory Compounds Present In the Diet: Classification And Mechanism Of Actionmentioning
confidence: 99%
“…In this context, terpenes are a highly diverse family of natural products which are synthesized by plants. This family have approximately 55,000 members with different chemical structures, presenting potential practical applications (Prakash, 2017;Serrano Vega et al, 2018). For this reason, it has been reported that terpenoids could ameliorate various symptoms caused by inflammation, inhibiting various steps of inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Plant terpenes have been shown to exhibit potential anti-in ammatory and antioxidant activity (González-Burgos et al, 2012; Vega et al, 2018;Li et al, 2019). In this study, the observation that TRDF and TREF ameliorated LPS-induced production of in ammatory cytokines and restored antioxidant enzyme activity may be attributed to the anti-in ammatory and antioxidant activities of the terpenes present in the fractions.…”
Section: Discussionmentioning
confidence: 56%